Parental concern regarding obesity in children with autism spectrum disorder in the United States: National Survey of Children's Health 2016. Issue 1 (January 2019) - Tybor, David J.; Eliasziw, Misha; Kral, Tanja V.E.; Segal, Mary; Sherwood, Nancy E.; Sikich, Linmarie; Stanish, Heidi; Bandini, Linda; Curtin, Carol; Must, Aviva
Abstract: Background: The prevalence of obesity in children with autism spectrum disorder (ASD) exceeds that of the general population, but the level of parental concern about obesity in these children is unexplored. Objective: We estimate the prevalence of obesity in children 10–17 years in the redesigned National Survey of Children's Health (NSCH) 2016, and compare parental concern about obesity between parents of children with and without ASD. Methods: The nationally representative NSCH 2016 oversampled parents of children with parent-report of special health care needs, including ASD. Parents opted to complete the survey via the web or surface mail. Following report of their child's height and weight, parents were asked "Are you concerned about their weight?" Response options included: "Yes, it's too high, " "Yes, it's too low, " or "No, I am not concerned." Obesity (>95th percentile BMI) was defined using the 2000 CDC growth reference. We used logistic regression to compare odds of obesity, and odds of parental concern, between children with and without ASD. Results: In 24, 251 children, ASD (n = 699) increased obesity risk after adjusting for age, sex, and race/ethnicity (OR = 1.54, 95%CI: 1.11, 2.14). ASD medication did not significantly affect obesity. ASD increased obesity concern (OR = 2.17, 95%CI: 1.53, 4.81) among parents with obese children. Parents of boys with obesity and ASD had less obesity concern if he was taking medication for ASD (OR = 0.258, 95%CI: 0.09, 0.78). Conclusion: While the prevalence of obesity is elevated in children with ASD, parental obesity concern is high, suggesting opportunities for the development of parent-focused obesity prevention and treatment interventions for this population.